How Radar Technology Changed the Course of the World after World War II - Science and Technology - Pun, Sirjana (Unity Journal, 2021)
After the independent invention of radar in the early 1930s, the development of radar went rapidly during World War II (1939-1945) when both Axis and Allied forces relied on the system to get an edge over the other. Ever since the war, radar technology has substantially increased in its innovation and capability throughout the years. This paper examines the progress of radar technology following World War II (1939-1945) with an aim to provide a landscape of the prevalent radar system during the war which was mono-pulse tracking radar systems and moving-target indication (MTI) system. After a thorough background study of the past radar system, the paper highlights application of the newer developed Phased Array Radar System which was formulated out through the implementation of the improved capabilities of both prevalent systems. Moreover, the paper provides a brief overview of the modular system and formulates a time frame relating to the development of radar research. Thus, the paper, later on, foresees the prominent future where phased array systems could be expanded to civilian and non-civilian technological research by providing thorough research and comparative analysis. Phased array systems are found to a prominent possible cheaper alternative for the civilian and non-civilian system. It shows prominence to be an effective useful tool for radar systems.